Numerical investigation of exhaust gas reforming of natural gas for on-board hydrogen-rich syngas production in spark ignition engine - Abdulwahid, Omar Arman (2021)
Exhaust gas reforming is an attractive method for performance enhancement of internal combustion engines fuelled by natural gas since syngas can be generated inline from the reforming process to overcome the hydrogen storage issue. The aim of this study was to model and simulate exhaust gas reformer for on-board hydrogen-rich syngas production and study the effect of the reformed gas on the combustion characteristics of the engine. The study was carried out at 100% engine load, and the engine speeds were varying from 1,200 to 3,000 rpm with an interval of 300 rpm. Firstly, 1D Modelling was used to observe the reforming characteristics to determine the amount of needed catalyst and natural gas (CH4) flow rate to achieve the highest possible reforming performance. Secondly, CCD (central composite design) RSM (response surface method) optimization was used to obtain the maximum methane conversion and syngas production at one minimum methane flow rate and catalyst weight at all the engine speeds. Thirdly, the reformer dimensions were selected, and 2D CFD simulation was conducted to investigate the reforming characteristics of the sized reformer model. Moreover, the reforming characteristics were evaluated at various conditions. Finally, 3D CFD simulation of the engine was conducted to study the effect of the reformed gas on the combustion characteristics and compared with purely natural gas using dual fuelling system. The 1D Modelling showed that as the engine speed increased, less amount of catalyst is needed, and a higher amount of natural gas is required. The demanded amount of catalyst mass and natural that determined by using RSM CCD was 850 g and 35 mol/hr, respectively. 2D CFD simulation found that the maximum methane conversion and syngas production were obtained at 3,000 rpm and 2,100 rpm, respectively. Increasing the rate of recirculated exhaust gas resulted in higher consumption of methane and the generation of H2 and CO. Steam addition enhanced methane conversion. However, when the amount of steam exceeded that of methane, less hydrogen was produced. At the same time, the rise of the wall temperature increased the methane conversion and reduced the H2/CO ratio. The air addition increased methane conversion and reduced the amount of produced hydrogen in the syngas mixture. Lastly, 3D CFD simulation of the combustion characteristics showed that the addition of the reformed gas contributed to higher in-cylinder pressure and rate of heat release as well which is considered as a sign of better combustion characteristics than purely natural gas. Overall, the numerical investigation demonstrated that the amount of syngas generated through exhaust gas reforming process was sufficient to achieve a significant enhancement in the SI engine combustion fuelled by natural gas.